Factors affecting the dissociation of metal ions from humic substances. (2nd January 2018) - Bryan, Nick; Jones, Dominic; Keepax, Rose; Farrelly, Dean; Abrahamsen, Liam; Beard, Rebecca; Li, Nigel; Weir, George
Abstract: Previously, it has been suggested that metal ions complexed to humic acid in the environment might show slower dissociation than those added to humic substances in the laboratory, which has serious implications for the transport of radionuclides in the environment. The dissociation of lanthanide and anthropogenic actinide ions from humic substance complexes has been studied as a function of humic concentration and metal ion:humic concentration ratio. The results suggest that the apparently slower kinetics observed for metal ions complexed in the environment are probably due to the large humic concentrations that are used in those studies. Further, there is no evidence that the dissociation rate constant varies at very low metal ion concentrations. Although humic samples size-fractionated by ultrafiltration showed that more metal may be bound non-exchangeably, there was no evidence for different rate constants. Ultrafiltration of Eu(III)/humic acid mixtures did show a shift in Eu from smaller to larger fractions over a period of two days. Therefore, the results suggest that dissociation rate constants determined in the laboratory at metal ion concentrations higher than those expected in the environment may be used in predicting radionuclide mobility, provided that the humic acid concentration is in the range expected at the site.